Solvent-free NMC electrodes for Li-ion batteries: unravelling the microstructure and formation of the PTFE nano-fibril network - Matthews, G. A. B.; Wheeler, S.; Ramírez-González, J.; Grant, P. S. (Frontiers in Energy Research, 2024)
The microstructure and electrochemical performance of solvent-free processed and slurry cast Li(Ni0.6Co0.2Mn0.2)O2 (NMC622) based electrodes for Li-ion batteries has been investigated. In contrast to a moss-like PVDF-based carbon binder domain in slurry cast electrodes, the PTFE binder in solvent-free electrodes had a hierarchical morphology composed of primary fibrils of a few µm in diameter and 100’s µm in length that branched into secondary and then ever finer fibrils, down to diameters of 10s nm or below. A mechanism for the formation of the branch-like morphology observed in PTFE-based solvent-free electrodes is also presented. Even the finest fibrils were confirmed to survive typical cathode cycling conditions. The solvent-free electrodes showed progressive improvement in capacity with increasing charge-discharge rate (up to 150% at 2C) compared with slurry cast equivalents. The capacity of solvent-free electrodes faded 40% slower over 200 cycles at C/3. Impedance analysis showed the solvent-free microstructure enabled reduced charge transfer resistance and ionic resistance, arising from minimal obscuration of the active material surface and no pore blockage.